1972
DOI: 10.1136/bmj.4.5842.694
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Blood Pressure, Renin, and Angiotensin after Bilateral Nephrectomy in Patients with Chronic Renal Failure

Abstract: SummaryCirculating levels of renin, angiotensin I, and angiotensin II were increased in six patients with chronic renal failure and hypertension uncontrolled by dialysis and hypotensive drugs. Lower and often normal levels were found in 10 patients whose blood pressure was controlled by dialysis treatment. For a variety of reasons all patients were subjected to bilateral nephrectomy. The logarithm of the decrease in plasma concentrations of renin and angiotensin II was significantly related to the fall of bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 18 publications
2
12
1
Order By: Relevance
“…Thus, our results are in accordance with others who also found low renin levels in a few corresponding patients [1,2,4,5,11,24,25,33,41,43,44]. It has been suggested [341 on the basis of present knowledge on inactive renin that the detection of renin in plasma of anephric patients could at least partly be ascribed to the inadvertent activation of inactive renin in vitro either by cryoactivation during sampling of plasma in chilled tubes or by the use of a renin determination method which applied acidification.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Thus, our results are in accordance with others who also found low renin levels in a few corresponding patients [1,2,4,5,11,24,25,33,41,43,44]. It has been suggested [341 on the basis of present knowledge on inactive renin that the detection of renin in plasma of anephric patients could at least partly be ascribed to the inadvertent activation of inactive renin in vitro either by cryoactivation during sampling of plasma in chilled tubes or by the use of a renin determination method which applied acidification.…”
Section: Discussionsupporting
confidence: 95%
“…It has been suggested [341 on the basis of present knowledge on inactive renin that the detection of renin in plasma of anephric patients could at least partly be ascribed to the inadvertent activation of inactive renin in vitro either by cryoactivation during sampling of plasma in chilled tubes or by the use of a renin determination method which applied acidification. This might in part explain why some authors reported even normal renin values in some anephric patients [5,11,24,25,44]. In the present study, we found active renin in such patients using a PRC determination method in which such activation steps are excluded.…”
Section: Discussioncontrasting
confidence: 50%
“…Our experience, based on the 9 patients with uncontrollable hypertension who underwent bilateral nephrectomy, leads US to support the view that this procedure produces a dramatic lowering of the blood pressure in selected patients and can be life-saving. We have found (Gleadle et al, 1969;Medina et al, 1972) that very high plasma renin or angiotensin 11 levels are of value in predicting a good blood pressure response to nephrcctomy, and this has also been the experience in other centres (Lazarus et al, 1972;Mahoney et al, 1972). Estimates of the incidence of this uncontrollable form of hypertension vary and in our experience these patients constitute about 5 per cent of the dialysis population.…”
Section: Discussionsupporting
confidence: 66%
“…The mechanisms underlying increased SNA in CKD are not completely understood. Several studies have reported an attenuation of SNA and blood pressure (BP) following bilateral nephrectomy (Medina et al, 1972; Getts et al, 2006; Gawish et al, 2010). This has founded the concept that the trigger of the enhanced central sympathetic outflow in CKD patients resides in the affected kidneys themself.…”
Section: Introductionmentioning
confidence: 99%